FRI0608 ASSOCIATION BETWEEN INTERSTITIAL LUNG DISEASE AND RHEUMATIC DISEASE: IMPLICATIONS IN CLINICAL PRACTICE. (June 2019) - Ortiz-Santamaria, Vera; Oto, Noelí Reguart; Dios, Pau Sendra de; Busquets, Noemí; Pascual, Maria; Ponce, Andrés; Surís, Xavier; Galea, Yolanda; Mola, Anna; Torrella, Marta; Tarrega, Julia; Barbeta, Enric
Abstract : Background: The relationship between interstitial lung disease (ILD) and rheumatic diseases is well known. Recently, a new clinical entity has been described that relates ILD with autoimmune findings, IPAF (Interstitial Pneumonia with Autoimmune Features), which allows identifying and condensing non-cataloged diseases with pulmonary and rheumatic involvement. Objectives: Our aim is to establish which patients with ILD have a rheumatic disease, and which of them meet the IPAF criteria. We analyzed the role of nailfold capillaroscopy in these patients. Methods: This is a prospective descriptive observational study. The observation period was 2 years (2016-2018), in a county university hospital. Patients diagnosed with ILD of unknown etiology, derived from Pneumology Service, were included. A medical history was obtained focused on autoimmune disease, rheumatological evaluation, rheumatological blood markers and nailfold capillaroscopy, in order to establish whether they had a concomitant rheumatic disease. Results: Thirty patients with ILD were evaluated, with a mean age of 70, 5 years (53 - 88). Of the 30 subjects, 12 (40%) had usual interstitial pneumonia (UIP), 11 (36.67%) had organizing pneumonia (OP) and 7 (23.33%) had nonspecific interstitial pneumonia (NSIP). Eleven (36, 67%) of the 30 patients had an altered capillaroscopy, 6 of them (54, 5%) had a rheumatic disease. In our sample, 5 cases meet diagnostic IPAF criteria, 4 OP and 1 UIP, three of them with altered capillaroscopy. Conclusion: In our serie, one third of the patients were diagnosed with rheumatic disease associated with interstitial lung disease. Of the thirty evaluated patients, 36.67% had altered capillaroscopy, 54.5% presenting concomitant rheumatic disease. Following the IPAF classification criteria, we obtained 5 cases in our sample: four OP and one UIP, 3 of them with altered capillaroscopy. It is important to be aware of this association with a multidisciplinary approach for the adequate diagnosis and follow-up of these patients. Disclosure of Interests: Vera Ortiz-Santamaria Speakers bureau: GSK, Roche, Pfizer, MSD, Noelí Reguart Oto: None declared, Pau Sendra de Dios: None declared, Noemí Busquets: None declared, Maria Pascual: None declared, Andrés Ponce Speakers bureau: Abbie, Roche, Pfizer, MSD, Xavier Surís Speakers bureau: Lilly, Pfizer, MSD, Yolanda Galea: None declared, Anna Mola: None declared, Marta Torrella: None declared, Julia Tarrega: None declared, Enric Barbeta Speakers bureau: GSK, Boehringer Ingelheim, Roche